Holocene evolution of the southern Tauranga Harbour. Issue 4 (2nd October 2017) - MacPherson, David; Fox, Bethany R. S.; de Lange, Willem P.
ABSTRACT: Tauranga Harbour is a major economic centre and home to New Zealand's largest port. Despite the importance of the harbour basin, and especially of the shipping channel, the subsurface stratigraphy of this area has not been studied in detail. We use sediment cores retrieved in support of a recent dredging campaign to characterise the subsurface stratigraphy and interpret the sediments in terms of paleoenvironment. Four main facies (volcanic sand, lithic silt, coarse sand and pumiceous sand) were identified using textural, mineralogical and geochemical characteristics. They represent distinct depositional environments at different stages of the Holocene marine transgression (HMT). The oldest facies, deposited prior to the HMT (volcanic sand and lithic silt facies), represent the channel and overbank deposits of an aggrading river system with rapidly migrating channels. During the deposition of this facies, a change in sediment source is evident from geochemical data. This preceded a transition to a predominantly offshore sediment source (coarse sand facies), likely supplied by longshore drift from the Kaituna River, which was associated with the development of Mt Maunganui tombolo and Matakana barrier island. During the Holocene stillstand, the barrier island and tombolo restricted sediment input from offshore, resulting in the deposition of a predominantly locally derived unit (pumiceous sand facies), which still dominates sedimentation in the harbour today.